Tailored acidic deep eutectic solvents: A multifunctional co-catalyst mediating homogeneous catalysis and heterogeneous separation of ethylene methoxycarbonylation. (1st February 2023) - Song, Jianhua; Xu, Lin; Wang, Xiaoping; Chen, Chonghao; Wang, Weichong; Long, Haoyu; Nawaz, Muhammad Asif; Liu, Dianhua
Graphical abstract: Homogeneous catalysis and heterogeneous separation Highlights: Homogeneous catalysis and heterogeneous separation were achieved using HPSADESs. HPSADESs were used as multifunctional cocatalyst for methoxycarbonylation. Pd(Ⅱ) and ligands in the product can be extracted by rationally designed HPSADESs. No significant decrease in catalytic activity and selectivity within 20 runs. A protocol for preparing halogen-poor strong acidic DESs (HPSADESs) was proposed. Abstract: In classical homogeneous catalysis with noble metals as catalysts, catalyst separation is a major obstacle of its widespread application. It has by far still a challenge to establish a highly effective and easy-to-separate system in a rational manner. Herein, rationally tailored acidic deep eutectic solvents (ADESs) were applied as acid promoter, phase separator, and extractant in Pd-catalyzed methoxycarbonylation of ethylene, resulting in high catalytic activity and selectivity as well as long-term stability towards the desired methyl propionate (MP), along with the homogeneous catalysis and heterogeneous separation. This work represents an elegant and advanced methodology in the area of catalyst recycling, the deeper insights put forward in text are meaningful for further exploration of abundant industrial applications and deep eutectic solvents (DESs) design.